MDCT and MR Imaging of Acute Abdomen New Technologies and Emerging Issues (Springer International Publishing, 2018)
This superbly illustrated book describes a comprehensive and modern approach to the imaging of abdominal and pelvic emergencies of traumatic and non-traumatic origin. The aim is to equip the reader with a full understanding of the roles of advanced cross-sectional imaging modalities, including dual-energy computed tomography (DECT) and magnetic resonance imaging (MRI). To this end, recent literature on the subject is reviewed, and current controversies in acute abdominal and pelvic imaging are discussed. Potential imaging and related pitfalls are highlighted and up-to-date information provided on differential diagnosis. The first two chapters explain an evidence-based approach to the evaluation of patients and present dose reduction strategies for multidetector CT imaging (MDCT). The remaining chapters describe specific applications of MDCT, DECT, and MRI for the imaging of both common and less common acute abdominal and pelvic conditions, including disorders in the pediatric population and pregnant patients. The book will be of value to emergency and abdominal radiologists, general radiologists, emergency department physicians and related personnel, general and trauma surgeons, and trainees in all these specialties.